Accurate evaluation of blackening disease in lotus (Nelumbo nucifera Gaertn.) using a quantitative PCR-based assay for Hirschmanniella diversa Sher and H. imamuri Sher. (January 2021) - Kurashita, Hazuki; Kuroda, Kyohei; Narihiro, Takashi; Takagi, Motonori; Goto, Maki; Ikeda, Shoji; Hirakata, Yuga; Hatamoto, Masashi; Maki, Shinya; Yamaguchi, Takashi; Aoi, Toru
Abstract: Blackening and deformation disease (called " kurokawa-senchu-byo " in Japanese) of lotus ( Nelumbo nucifera Gaertn.) is a critical issue in lotus cultivation that is known to be caused by the plant-parasitic nematodes Hirschmanniella diversa Sher and H. imamuri Sher. To evaluate the extent of the disease, a damage index that classifies the nematode damage into five stages according to the surface condition of the lotus tubers has been proposed; however, this method requires considerable experience to perform an accurate evaluation. In this study, we quantified H. diversa and H. imamuri populations using a 5.8S ribosomal RNA (rRNA) gene/internal transcribed spacer (ITS) region-targeted quantitative PCR (qPCR) technique in lotus root and soil samples collected from 24 fields in Japan. We attempted to reveal the relationship between the damage index values and the abundance of lotus-parasitic nematodes based on the gene copy numbers of the 5.8S rRNA/ITS region in order to predict the in situ contamination level of lotus cultivation fields. Through the use of template DNA extracted from lotus roots, we successfully detected both H. diversa and H. imamuri at 6.8 ± 0.24 and 5.0 ± 0.32 log10 copies/g-fresh lotus root, respectively. Moreover, many large variations as well as samples in which Hirschmanniella spp. were not detected were observed in the soil samples, indicating that using lotus root-derived DNA could more precisely quantify the abundance of plant-parasitic nematodes in the lotus cultivation fields. Linear regression analyses showed a strong correlation between the density of H. diversa and the damage index values, while there was no significant correlation between the H. imamuri density and the damage index values. These results indicate that H. diversa, rather than H. imamuri, may act as a major causative agent of " kurokawa-senchu-byo " in lotus cultivated in Japan and that 6.4 log10 copies/g-fresh lotus root of H. diversa density represents an economic injury level (damage index = 2) for lotus cultivation. Highlights: Using lotus root-derived DNA could more precisely quantify lotus-parasitic nematodes. Hirschmanniella diversa may act as a major causative agent of " kurokawa-senchu-byo ". There is no significant correlation between densities of H. imamuri and damage index. 6.4 log10 copies/g-fresh lotus root of H. diversa densities is an economic injury level.